(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Human Resource Management (HRM) is crucial in the hospitality sector, particularly in hotel management, where employee satisfaction directly influences guest experiences and operational efficiency. This study emphasizes the importance of improving HR practices to address challenges such as high turnover rates, inadequate training, and employee engagement. By adopting effective HR strategies, hotels can enhance employee retention, satisfaction, and overall service quality, ultimately leading to better business outcomes. The research employs a mixedmethods approach, combining quantitative surveys and qualitative interviews to gather comprehensive insights into current HR practices and their impact on hotel management.